"I didn't really understand it, I just thought it'd help": exploring the motivations, understandings and experiences of patients with advanced lung cancer participating in a non-placebo clinical IMP trial. Issue 1 (December 2016) - Harrop, Emily; Noble, Simon; Edwards, Michelle; Sivell, Stephanie; Moore, Barbara; Nelson, Annmarie
Abstract Background Few studies have explored in depth the experiences of patients with advanced cancer who are participating in clinical investigational medicinal product trials. However, integrated qualitative studies in such trials are needed to enable a broader evaluation of patient experiences in the trial, with important ethical and practical implications for the design and conduct of similar trials and treatment regimes in the future. Methods Ten participants were recruited from the control and intervention arms of FRAGMATIC: a non-placebo trial for patients with advanced lung cancer. Participants were interviewed at up to three time points during their time in the trial. Interviews were analysed using Interpretive Phenomenological Analysis. Results Patients were motivated to join the trial out of hope of medical benefit and altruism. Understanding of randomisation was mixed and in some cases poor, as was appreciation of trial purpose and equipoise. The trial was acceptable to and evaluated positively by most participants; participants receiving the intervention focused on the potential treatment benefits they hoped they would receive, whilst participants in the control arm found alternative reasons, such as altruism, personal fulfilment and positive attention, to commit to and perceive benefits from the trial. However, whilst experiences were generally very positive, poor understanding, limited engagement with trial information and focus on treatment benefits amongst some participants give cause for concern. Conclusions By exploring longitudinally the psychological, emotional and cognitive domains of trial participation, we consider potential harms and benefits of participation in non-placebo trials amongst patients with advanced lung cancer and identify several implications for future research with and care for patients with advanced cancer. Trial registration ISRCTN80812769 . Registered on 8 July 2005.